(untitled) (Journal of Comparative & International Higher Education, 2022)
The purpose of this qualitative study was to explore the experiences of China recruiters during the pandemic, particularly with their job stress and sense of job security. The study also explored the new norms of Chinese students’ recruitment post-pandemic crisis. Using qualitative analysis, we found that China recruiters experienced different stressors during the pandemic regardless of their working location. The participants recognized the importance of communication and seeking institutional support to help overcome their stress during the pandemic. They suggested that higher education administrators should be sensitive to the needs of their international recruiters. The participants also suggested several new norms for future recruitment, such as using the hybrid recruitment model, promoting university collaboration, initiating joint programs between US and Chinese institutions, and hiring domestic recruiters. Implications for practice are discussed.